Drug-related problem (DRP) penggunaan antidiabetik oral dan insulin pada pasien diabetes melitus tipe II rawat inap di RSU Royal Prima Medan - Elfia Neswita; Brian Elberth Halu; Razoki; Asyrun lkhairi Lubis; Muhammad Yunus; Nurasni; Octavian Ashido Nababan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Diabetes mellitus is a group of metabolic disorders characterised by hyperglycemia which is the cause of death of up to 80% in low- and middle-income countries. Type 2 diabetes mellitus is the most common form of diabetes. The goals of managing type 2 diabetes mellitus therapy are to reduce the risk of microvascular and macrovascular complications, reduce mortality, and improve quality of life. Treatment of diabetes mellitus requires a long time. Problems arising from complications in diabetes mellitus will increase the difficulty in treating patients. This can potentially cause issues related to Drug Related Problems (DRP). Drug-Related Problems refers to unexpected events experienced by patients and can interfere with the success of the drug therapy given. The research method in this study was to determine the drugs to be evaluated in the form of oral antidiabetic drugs used while undergoing type 2 diabetes mellitus therapy and insulin therapy. The results showed that 26 patients experienced Drug-Related Problems or not (50%). Six patients experienced actual Drug Related Problems (10.2%). In comparison, those who experienced Potential Drug Related Problems were 24 patients (46.15%) of a total of 52 patients with type 2 diabetes mellitus who were the sample of this study. Two categories of Drug Related Problems occur, namely Drug Related Problems related to additional drug therapy with a total of 2 incidents (2.17%) and Drug Related Problems related to unwanted drug reactions (Adverse Drug Reactions) with a total of 4 incidents (7,7%).